The sword law was seen from the Myanmar Military Coup which harmed society in response to International Law. - Magno, Feby Marcela Silva (Journal of ASEAN Dynamics and Beyond, 2023)
A coup is the overthrow of power against the ruler by illegal or even brutal means. And a coup is the key for an officer to seize power from the state which then becomes a military coup, and in developing countries the military always intervenes in the government that is in power. Unconstitutional in the form of coups, the military always intervenes in government functions in developing countries. One of the countries that frequently experienced coups, namely Myanmar in 1962, 1988–2021, was due to the desire of the Burmese military to maintain its existence or influence. The coup that took place in Myanmar was a coup that was controversial for all parties because the state or international or regional organizations are not allowed to intervene in the matter or issues, the state does not intervene based on the principles stated in the law, according to God. Resolving coup conflicts is difficult according to international law because there are already binding regulations.